PERANCANGAN MESIN PENGADUK PAKAN TERNAK SAPI DENGAN SISTEM SIRKULASI VERTIKAL MENGGUNAKAN SCREW DRIVER - Basyir, Abdul; Sinaga, Patar AP; Muldani, Muldani; Supriadi, Supriadi; Yulfitra, Yulfitra; lubis, Zulkifli; Barita, Barita; mahyunis, mahyunis (Jurusan Teknik Mesin, Fakultas Teknologi Industri, Institut Teknologi Medan (ITM), 2019)
Cows really need quality food, of course, a lot of quality cow feed is obtained from the process of fermentation. For the implementation of cattle feed through the process of fermentation can not be separated from the stirring process or mixing the basic ingredients of feed added with other added ingredients. The purpose of the design: Planning the engine speed and driving power, planning the main components of the machine used, and finally making the draft work plan. The results of the conclusions from the discussion are: Engine rotation 290 (rpm), material density 481 kg / m3 with a capacity of 63 kg. Driving power 1.5 hp, 1450 rpm rotation, voltage = 220 V, frequency 50 Hz, 1 phase. Shaft material S 35 C, with a size of 25 mm. S 30 C peg material, peg size: 18.75 mm long, 8.75 mm wide. Cast iron material, size 3 and 10 inches. Belt material from teteron rubber, measuring 57 inches. Types of single row bearings contack ball bearings, No.7305, inner diameter = 25 mm, with age 32289244 (hours). Deflection occurs, y = 0.000029 mm, the frame is safe to use because the load that occurs is less than the allowable load (138